Differences in Emoji Usages Based on Self-Presentation Strategies and Motivations on Social Media and Their Role in Persuasive Messages - Alnasrallah, Lina Fawaz; Alselim, Heyla Abdullah (Journal of Educational and Psychological Sciences, 2024)
The study aimed to investigate the differences in emoji usages based on self-presentation strategies and motivations on social media and their role in persuasive messages. A comparative descriptive approach was used on a sample of 258 students from universities in Saudi Arabia. A content analysis of a group chat for King Saud University students via Telegram revealed the most used emoji through the Visual Studio text writing program. Measures of motivations for using social media, self-presentation strategies on social media, and the impact of emojis on persuasive messages were used. The study found differences between users of "crying and laughter emojis" in the self-focus motive (personal identity) favoring users of "crying emoji", with no differences in the relationship maintenance motive (social identity). The results also indicate differences between users of "crying and laughter emojis" in the self-disclosure (life streaming) strategy favoring users of "crying emoji", with no differences in other strategies (self-promotion, acceptance seeking, cautious self-presentation, positive impression management, depth self-disclosure (mind casting). Additionally, the study highlighted differences in the impact of Emojis that reflect "laughter, crying, sadness, requesting, and hoping" on both persuasiveness levels for seeking help and subscribing to the marketing offer. Finally, the findings revealed differences in the use of "crying emoji" favoring females, and "laughter emoji" favoring males. It is recommended to explore cultural and personality-based differences in emoji usage and conduct research on diverse societal samples.
Keywords: Emojis; Social Media; Persuasive Messages; Self-Presentation; Identity